Perwujudan Pemilu yang Luberjurdil melalui Validitas Daftar Pemilih Tetap - Risdiana Izzaty; Xavier Nugraha (Jurnal Suara Hukum, 2019)
In Article 22E paragraph (1) of the 1945 Constitution of the Republic of Indonesia, it is explained that General Elections (Elections) are held based on the principle of œluberjudil (direct, general, free, confidential, honest and fair). One of the manifestations of this principle is through the final voter list in the implementation of the election. This research is normative research with statute approach and conceptual approach. The issues discussed in this study are 1. Can the validity of the Permanent Voters List be seen as a manifestation of a direct, general, free, confidential, honest and fair election? 2. What are the problems that arise in determining the Permanent Voters List? 3. How is the guarantee of political rights for citizens due to problems that arise in the determination of the Permanent Voters List? Based on this research, it was found that the validity of the Permanent Voters List was part of the realization of the election system which was direct, general, free, confidential, honest and fair. This research also describes the problems in determining the Permanent Voters List and the mechanism for protecting the political rights of citizens in the event of problems in the final voter list